Freudig in die Schlacht - Emotionen als Codes für die recta intentio im gerechten Krieg (8.- 10. Jahrhundert) - Foerster, Anne (Emotionen im Krieg - Krieg der Emotionen)

The Swineherd’s Wife who Scolded the King - Foerster, Anne (Women in Early Medieval England)

Eadburh of Wessex - Foerster, Anne (Women in Early Medieval England)

Seaxburh - Foerster, Anne (Women in Early Medieval England)

The Interplay of Sound Tapestry and Music in the 1992 German Radio Play Adaptation of J.R.R. Tolkien’s The Lord of the Rings - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Word, Sound and Music in Radio Drama: An Introduction - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)

Struktur und Sonderbauten der Silberbergbaustädte des 16. Jahrhunderts. Zur Korrelation von Städtebau und Montanwesen (Potosí und das Erzgebirge) - Silvestri, Marco (Bergbau und Hausbau)

Word, Sound and Music in Radio Drama

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (arXiv:2401.02368)
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Hilfst du mir, so hilfst du dir. Diplomatische Überzeugungsstrategien der Regentin Christine Charlotte von Ostfriesland gegenüber Kaiser Leopold I. im 17. Jahrhundert (erscheint 2024) - Becker, Rieke (Österreichische Zeitschrift für Geschichtswissenschaften. Themenband „New Diplomatic History“)
Keywords: New Diplomatic History; Neue Diplomatiegeschichte

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

BelgienNet – une plateforme pour l’accès aux langues et cultures de la Belgique - Huybrechts, Yves; Karaca, Resul (Synergies Pays germanophones)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

„Es nimmt der Raum gastfreundlich auf die Menge“. Theodor Hells Prolog zur Eröffnung des Dresdner Hoftheaters (1841) - Eke, Norbert Otto (Die Kunst der Theatereröffnung. Ästhetik und Sozialgeschichte von Bühnenprologen)

Historisches Lernen in einer ‚(Geschichts-)Kultur der Digitalität‘? - Hartung, Olaf (Geschichtskulturen im digitalen Wandel?)

Geschichtskulturen im digitalen Wandel?

Het verhaal van Vlaanderen. Analyse van het mediaformat en het geschiedverhaal - Huybrechts, Yves; Schmitz, Sabine (bmgn — Low Countries Historical Review)

Fast Multiobjective Gradient Methods with Nesterov Acceleration via Inertial Gradient-Like Systems - Sonntag, Konstantin; Peitz, Sebastian (Journal of Optimization Theory and Applications)
We derive efficient algorithms to compute weakly Pareto optimal solutions for smooth, convex and unconstrained multiobjective optimization problems in general Hilbert spaces. To this end, we define a novel inertial gradient-like dynamical system in the multiobjective setting, which trajectories converge weakly to Pareto optimal solutions. Discretization of this system yields an inertial multiobjective algorithm which generates sequences that converge weakly to Pareto optimal solutions. We employ Nesterov acceleration to define an algorithm with an improved convergence rate compared to the plain multiobjective steepest descent method (Algorithm 1). A further improvement in terms of efficiency is achieved by avoiding the solution of a quadratic subproblem to compute a common step direction for all objective functions, which is usually required in first-order methods. Using a different discretization of our inertial gradient-like dynamical system, we obtain an accelerated multiobjective gradient method that does not require the solution of a subproblem in each step (Algorithm 2). While this algorithm does not converge in general, it yields good results on test problems while being faster than standard steepest descent.

A Descent Method for Nonsmooth Multiobjective Optimization in Hilbert Spaces - Sonntag, Konstantin; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Volkwein, Stefan (arXiv:2402.06376)
The efficient optimization method for locally Lipschitz continuous multiobjective optimization problems from [1] is extended from finite-dimensional problems to general Hilbert spaces. The method iteratively computes Pareto critical points, where in each iteration, an approximation of the subdifferential is computed in an efficient manner and then used to compute a common descent direction for all objective functions. To prove convergence, we present some new optimality results for nonsmooth multiobjective optimization problems in Hilbert spaces. Using these, we can show that every accumulation point of the sequence generated by our algorithm is Pareto critical under common assumptions. Computational efficiency for finding Pareto critical points is numerically demonstrated for multiobjective optimal control of an obstacle problem.

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

“A Short Introduction to the Film Glove and Touch Studies.” - Kraft, Kerstin

Die Vorgeschichte der „sozialen Medien“. Über die Träume digitaler Vergemeinschaftung und freier Kommunikation - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Sind „soziale Medien“ überhaupt ein Thema für die Geschichtswissenschaft? Ja, denn die längere Geschichte der Digitalisierung, in der die „sozialen Medien“ einzuordnen sind, zählt bereits über 80 Jahre. Konrad Zuse und andere Ingenieure entwickelten seit 1941 die ersten Digitalcomputer, Unternehmer*innen, Wissenschaftler*innen und Staatenlenker*innen setzten diese seit den 1950er Jahren für ihre Zwecke ein, die Zivilgesellschaft adaptierte sie in den darauffolgenden Dekaden – all das prägte die sozio-digitale Landschaft der späteren „sozialen Medien“. Als unmittelbar „nach dem Boom“ etwa um 1970 zahlreiche Industriegesellschaften einen strukturellen Wandel in Wirtschaft, Gesellschaft und Politik durchlebten, war eine Antwort darauf die vermehrte Digitalisierung und Vernetzung. Daraus entwickelte sich die 1990er Jahre als markante Dekade von World Wide Web, Google und Chatdiensten. Die Entwicklung der „sozialen Medien“ ist also unter anderem in eine ökonomische und gesellschaftliche Entwicklung der Aufmerksamkeitsökonomie und in die längeren Veränderungen von Wirtschafts- und Gesellschaftsordnungen der Ausdifferenzierung und partiellen Individualisierung seit den 1960er Jahren einzuordnen. Dadurch lässt sich besser verstehen, welche Prämissen ihnen zugrunde lagen, welche Möglichkeitsräume und Probleme sich daraus ergaben und warum sie die heutige Öffentlichkeit in einer bestimmten Art und Weise dominieren – ohne sie jedoch zu determinieren.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; World Wide Web; Digitalisierung

Alles geht? Die jüngste Geschichte der „sozialen Medien“. Zwischen Wirtschaft und Gemeinschaft - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Twitter ist jetzt X und befindet sich auf dem absteigenden Ast. Auf diesem Ast sitzt Facebook bereits seit längerem. Der Kurzvideodienst Vine, Vorgänger von TikTok, ist Geschichte. Und auch bei Google klingeln die Alarmglocken angesichts der „neuen“ Konkurrenz durch Microsoft und ChatGPT. Umso dringlicher wird also die Historisierung der „sozialen Medien“, das heißt, sie in ihren historischen Kontext einzuordnen und ihren Mythos zu entzaubern. Dabei wartet das Vorhaben mit einer doppelten Herausforderung auf: Erstens, dass es sich bei den Unternehmen der Branche und zweitens auch bei den dort gebildeten Gemeinschaften um recht flüchtige, wandelhaften Gestalten handelt. Scheitern und Wandel ist Teil der „sozialen Medien“ – und sei es nur in der schnellen Abfolge der Moden des „nächsten großen Dings“. Dementsprechend versucht dieser Beitrag mit einem systematischeren Ansatz als dem der gesellschaftlichen Selbstbeschreibung, die Entwicklung des sozio-digitalen Phänomens „soziale Medien“ in dessen Zeitkontext einzuordnen.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; Wirtschaftsgeschichte; Digitalisierung; Twitter; Facebook; Meta

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Zur Abscheidung von Tröpfchen-Aerosolen in filternden Abscheidern - Hassel, Richard

Using Worked Examples for Engaging in Epistemic Programming Projects - Hüsing, Sven; Schulte, Carsten; Sparmann, Sören; Bolte, Mario (Proceedings of the 55th ACM Technical Symposium on Computer Science Education V. 1)

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Answering legal questions from laymen in German civil law system - Büttner, Marius; Habernal, Ivan (Proceedings of the 18th Conference of the European Chapter of the Association for Computational Linguistics (Volume 1: Long Papers))
What is preventing us from building a NLP system that could help real people in real situations, for instance when they need legal advice but don{’}t understand law? This question is trickier than one might think, because legal systems vary from country to country, so do the law books, availability of data, and incomprehensibility of legalese. In this paper we focus Germany (which employs the civil-law system where, roughly speaking, interpretation of law codes dominates over precedence) and lay a foundational work to address the laymen{’}s legal question answering empirically. We create GerLayQA, a new dataset comprising of 21k laymen{’}s legal questions paired with answers from lawyers and grounded to concrete law book paragraphs. We experiment with a variety of retrieval and answer generation models and provide an in-depth analysis of limitations, which helps us to provide first empirical answers to the question above.

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

Ein Beitrag zur Erarbeitung von Fertigungsrichtlinien für das Kunststoff Freiformen - Hirsch, Andre

Experimentelle und simulative Analyse der Mischwirkung in Einschneckenextrudern - Schadomsky, Michael

Non-abelian $p$-adic Rankin-Selberg $L$-functions and non-vanishing of central $L$-values - Januszewski, Fabian (To appear in the American Journal of Mathematics)
We prove new congruences between special values of Rankin-Selberg $L$-functions for $GL(n+1)×GL(n)$ over arbitrary number fields. This allows us to control the behavior of $p$-adic $L$-functions under Tate twists and to prove the existence of non-abelian $p$-adic $L$-functions for Hida families on $GL(n+1)×GL(n)$. As an application, we prove strong non-vanishing results for central $L$-values: We give sufficient local conditions for twisted central Rankin-Selberg $L$-values to be generically non-zero.

Locally algebraic representations and integral structures on the cohomology of arithmetic groups - Januszewski, Fabian
This paper introduces the notion of locally algebraic representations and corresponding sheaves in the context of the cohomology of arithmetic groups. These representations are particularly relevant for studying integral structures and special values of cohomological automorphic representations, as well as corresponding period relations. We introduce and investigate related concepts such as locally algebraic $(\lieg,K)$-modules and cohomological types of automorphic representations. Applying the recently developed theory of tdos and twisted $\mathcal D$-modules, we establish the existence of canonical global $1/N$-integral structures on spaces of automorphic cusp forms. As an application, we define canonical periods attached to regular algebraic automorphic representations, potentially related to the action of Venkatesh's derived Hecke algebra on cuspidal cohomology.

Anwendung von System Dynamics zur Geschäftsmodellinnovation in einem B2B-Ökosystem - Ksouri-Gerwien, Christoph; Vorbohle, Christian (Digitale Plattformen und Ökosysteme im B2B-Bereich)

A critical exponent in a quasilinear Keller–Segel system with arbitrarily fast decaying diffusivities accounting for volume-filling effects - Stinner, Christian; Winkler, Michael (Journal of Evolution Equations)
Abstract The quasilinear Keller–Segel system $$\begin{aligned} \left\{ \begin{array}{l} u_t=\nabla \cdot (D(u)\nabla u) - \nabla \cdot (S(u)\nabla v), \\ v_t=\Delta v-v+u, \end{array}\right. \end{aligned}$$ u t = ∇ · ( D ( u ) ∇ u ) - ∇ · ( S ( u ) ∇ v ) , v t = Δ v - v + u , endowed with homogeneous Neumann boundary conditions is considered in a bounded domain $$\Omega \subset {\mathbb {R}}^n$$ Ω ⊂ R n , $$n \ge 3$$ n ≥ 3 , with smooth boundary for sufficiently regular functions D and S satisfying $$D>0$$ D > 0 on $$[0,\infty )$$ [ 0 , ∞ ) , $$S>0$$ S > 0 on $$(0,\infty )$$ ( 0 , ∞ ) and $$S(0)=0$$ S ( 0 ) = 0 . On the one hand, it is shown that if $$\frac{S}{D}$$ S D satisfies the subcritical growth condition $$\begin{aligned} \frac{S(s)}{D(s)} \le C s^\alpha \qquad \text{ for } \text{ all } s\ge 1 \qquad \text{ with } \text{ some } \alpha < \frac{2}{n} \end{aligned}$$ S ( s ) D ( s ) ≤ C s α for all s ≥ 1 with some α < 2 n and $$C>0$$ C > 0 , then for any sufficiently regular initial data there exists a global weak energy solution such that $${ \mathrm{{ess}}} \sup _{t>0} \Vert u(t) \Vert _{L^p(\Omega )}<\infty $$ ess sup t > 0 ‖ u ( t ) ‖ L p ( Ω ) < ∞ for some $$p > \frac{2n}{n+2}$$ p > 2 n n + 2 . On the other hand, if $$\frac{S}{D}$$ S D satisfies the supercritical growth condition $$\begin{aligned} \frac{S(s)}{D(s)} \ge c s^\alpha \qquad \text{ for } \text{ all } s\ge 1 \qquad \text{ with } \text{ some } \alpha > \frac{2}{n} \end{aligned}$$ S ( s ) D ( s ) ≥ c s α for all s ≥ 1 with some α > 2 n and $$c>0$$ c > 0 , then the nonexistence of a global weak energy solution having the boundedness property stated above is shown for some initial data in the radial setting. This establishes some criticality of the value $$\alpha = \frac{2}{n}$$ α = 2 n for $$n \ge 3$$ n ≥ 3 , without any additional assumption on the behavior of D ( s ) as $$s \rightarrow \infty $$ s → ∞ , in particular without requiring any algebraic lower bound for D . When applied to the Keller–Segel system with volume-filling effect for probability distribution functions of the type $$Q(s) = \exp (-s^\beta )$$ Q ( s ) = exp ( - s β ) , $$s \ge 0$$ s ≥ 0 , for global solvability the exponent $$\beta = \frac{n-2}{n}$$ β = n - 2 n is seen to be critical.
Keywords: Mathematics (miscellaneous)

Zwischen Beutesuche und politischen Ambitionen. Die Normannen an Rhein und Maas zwischen 880 und 892 - Kamp, Hermann (Zeitschrift des Aachener Geschichtsvereins)

The Stellarium Gornergrat: Astrophysics with your own Data - Gschwind, Stéphane; Hohmann, Sascha; Müller, Andreas; Nordine, Jeffrey; Riesen, Timm-Emanuel (Journal of Physics: Conference Series)
Abstract Remote-controlled telescopes in education provide the opportunity to obtain high quality astronomy images for a broad variety of users. The Stellarium Gornergrat is such a telescope. In addition to pure observation, it offers a user-friendly interface and teaching modules so that astronomical and astrophysical projects can be integrated into everyday school life without any special prior knowledge and without requiring a lot of time. This contribution presents the Stellarium project and a provides an overview of several teaching activities.
Keywords: Computer Science Applications; History; Education

‚Schelmische‘ Post-DDR-Romane: Ingo Schulzes „Peter Holtz“ und Lea Streisands „Hufeland, Ecke Bötzow“ - Elit, Stefan (‚Topographisches‘ Schreiben: Lea Streisand, Paderborn, Wintersemester 2022/2023)

Characterizing Microheterogeneity in Liquid Mixtures via Local Density Fluctuations - Lass, Michael; Kenter, Tobias; Plessl, Christian; Brehm, Martin (Entropy)
We present a novel approach to characterize and quantify microheterogeneity and microphase separation in computer simulations of complex liquid mixtures. Our post-processing method is based on local density fluctuations of the different constituents in sampling spheres of varying size. It can be easily applied to both molecular dynamics (MD) and Monte Carlo (MC) simulations, including periodic boundary conditions. Multidimensional correlation of the density distributions yields a clear picture of the domain formation due to the subtle balance of different interactions. We apply our approach to the example of force field molecular dynamics simulations of imidazolium-based ionic liquids with different side chain lengths at different temperatures, namely 1-ethyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride, which are known to form distinct liquid domains. We put the results into the context of existing microheterogeneity analyses and demonstrate the advantages and sensitivity of our novel method. Furthermore, we show how to estimate the configuration entropy from our analysis, and we investigate voids in the system. The analysis has been implemented into our program package TRAVIS and is thus available as free software.

'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

‚Topographisches‘ Schreiben. Lea Streisand, Paderborn Wintersemester 2022/23: Die 41. Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Sich selbst erzählen. Lea Streisands autofiktionales Erzählen. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (arXiv:2404.02844)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyse these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterising their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterisation and certification tasks. By developing open-source customised algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of $10^6$. This requires finding $10^8$ elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of $10^{12}$ elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Asymptotic behavior of solutions to the extension problem for the fractional Laplacian on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Evolution Equations)
Abstract This work deals with the extension problem for the fractional Laplacian on Riemannian symmetric spaces G / K of noncompact type and of general rank, which gives rise to a family of convolution operators, including the Poisson operator. More precisely, motivated by Euclidean results for the Poisson semigroup, we study the long-time asymptotic behavior of solutions to the extension problem for $$L^1$$ L 1 initial data. In the case of the Laplace–Beltrami operator, we show that if the initial data are bi- K -invariant, then the solution to the extension problem behaves asymptotically as the mass times the fundamental solution, but this convergence may break down in the non-bi- K -invariant case. In the second part, we investigate the long-time asymptotic behavior of the extension problem associated with the so-called distinguished Laplacian on G / K . In this case, we observe phenomena which are similar to the Euclidean setting for the Poisson semigroup, such as $$L^1$$ L 1 asymptotic convergence without the assumption of bi- K -invariance.
Keywords: Mathematics (miscellaneous)

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Noctua 2 Supercomputer - Bauer, Carsten; Kenter, Tobias; Lass, Michael; Mazur, Lukas; Meyer, Marius; Nitsche, Holger; Riebler, Heinrich; Schade, Robert; Schwarz, Michael; Winnwa, Nils; Wiens, Alex; Wu, Xin; et al. (Journal of large-scale research facilities)
Noctua 2 is a supercomputer operated at the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. Noctua 2 was inaugurated in 2022 and is an Atos BullSequana XH2000 system. It consists mainly of three node types: 1) CPU Compute nodes with AMD EPYC processors in different main memory configurations, 2) GPU nodes with NVIDIA A100 GPUs, and 3) FPGA nodes with Xilinx Alveo U280 and Intel Stratix 10 FPGA cards. While CPUs and GPUs are known off-the-shelf components in HPC systems, the operation of a large number of FPGA cards from different vendors and a dedicated FPGA-to-FPGA network are unique characteristics of Noctua 2. This paper describes in detail the overall setup of Noctua 2 and gives insights into the operation of the cluster from a hardware, software and facility perspective.
Keywords: Noctua 2; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing